Utilizing social media in socioscientific issues discussion to improve argumentative skills and microbial literacy - herlanti, yanti; Rustaman, Nuryani; Fitriani, Any; Rohman, Ijang (Jurnal Inovasi Pendidikan IPA, 2023)
Microbial literacy plays an essential role in understanding microbiology issues. Discussion of socioscientific issues is one way to improve microbial literacy and argumentative skills. Socioscientific issues discussion takes a long time if applied in an inadequate classroom. Thus, social media is used as a tool to discuss socioscientific issues. This study aims to utilize social media Facebook' in discussing socioscientific issues. The research method used is quasi-experimental. The pre-post one group design was used to know the effect of socioscientific discussion on argumentation skills, and the pre and post-control group design was used to know the differences in microbiological literacy of students who discuss socioscientific issues and did not discuss socioscientific issues. Discussion of socioscientific issues is carried out through four steps: polemic, exploration, conclusion, and action. The results showed increased individual argumentation skills before and after discussing socioscientific issues via Facebook. Before the discussion there are 34.38% of students reached argumentation levels 4 to 5, after which 56.25% reached argumentation levels 4-5. Discussion of socioscientific issues through social media has made group argumentation skills reach higher performance (level 5). Microbiological literacy between groups discussing socioscientific issues and not discussing socioscientific issues showed no significant difference except for questions directly related to the topic of discussion, namely changes in perceptions of microbes. Online discussions of socioscientific issues with pro and con arguments were very effective through social media "Facebook."